Investigating the ability of methicillin-resistant Staphylococcus pseudintermedius isolates from different sources to adhere to canine and human corneocytes - Phumthanakorn, Nathita (Can J Vet Res, 2019)
Assays were done to assess the ability of 5 methicillin-resistant Staphylococcus pseudintermedius (MRSP) isolates from difference sources to adhere to canine and human corneocytes. Cell wall-associated (CWA) protein gene profiles were examined to look for associations with adherence. Five MRSP strains were studied: 3 with the same CWA protein gene profile (14 genes) and belonging to sequence type (ST) 45 were isolated from a dog, a human, and the environment. The other 2 were an environmental isolate belonging to ST433 that had the lowest number of CWA protein genes (12) and a canine clinical isolate belonging to ST733 that had the greatest number of CWA protein genes (18). The 3 isolates of MRSP ST45, a major clone in Thailand, had the greatest ability to adhere to canine and human corneocytes. Nevertheless, MRSP adherence ability could not be predicted from the profile of genes encoding CWA proteins.